ANALISIS PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. NUSANTARA SURYA SAKTI (NSS) STUDI KASUS DI CABANG KOTA PANGKALPINANG - Hariyanti, Dian Nova; Lestari, Deara Shinta; R. Manullang, Rizal (Jurnal Progresif Manajemen Bisnis, 2023)
This is an undergraduate thesis was written by Dian Nova Hariyanti, with student 250190071P, major in Management, entitled "ANALISIS PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. NUSANTARA SURYA SAKTI (NSS) STUDI KASUS DI CABANG KOTA PANGKALPINANG”. The results of the study show that the application of leadership style has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Work discipline has a partial and significant positive effect on employee performance. Simultaneously positive and significant effect between leadership style, motivation, work discipline on employee performance with a value of 182,362 ftable 3. 16.